Genetic and morphological variation in the Bulbophyllum exaltatum (Orchidaceae) complex occurring in the Brazilian “Campos Rupestres”: implications for taxonomy and biogeography - Ribeiro, Patricia Luz (Universidad de Costa Rica, 2015)
Bulbophyllum Thouars is a pantropical genus. It is one of the most species-rich genera of the Orchidaceae, with ca. 1.200 species (Dressler 1993). The genus pre- sents myophily (pollination by Diptera) as pollination syndrome. Because orchid species are mainly self- compatible, we expect that fly-pollinated orchids pre- sent low variability within the populations and high genetic differentiation among conspecific populations, due to the reduction of the gene flow (Borba & Semir 1998, Borba et al. 2001). This could help to explain the high number of species in genera of fly-pollinated orchids, most of them with restricted distribution.